Understanding visuals in the life sciences - Yu, Han 1980- (Understanding life series, 2024)
From photographs to micrographs, from the various types of graphs to fun, interactive visuals and games, there are many different forms in which science can be visualised. However, all of these forms of visualisation in the Life Sciences are susceptible to misunderstandings and misinformation. This accessible and concise book demonstrates the misconceptions surrounding the visuals used in popular life science communication. Richly illustrated in colour, this guide is packed with examples of commonly used visual types: photographs, micrographs, illustrations, graphs, interactive visuals, and infographics allowing visual creators to produce more effective visuals that aspire to being both attractive and informative for their target audience. It also encourages non-specialist readers to be more empowered and critical, to ask difficult questions, and to cultivate true engagement with science. This book is an invaluable resource for life scientists and science communicators, and anyone who creates visuals for public or non-specialist readers